Directional assist (0 1 0) plane growth in LiMnPO4 prepared by solvothermal method with polyols to enhance electrochemical performance - Xie, Qian; Zhu, Jihua; Wang, Chengyun; Fang, Kaibin; Yang, Wei; Liu, Quanbing; Wang, Yali; Chen, Shengzhou (Chinese journal of chemical engineering, 2021)
[Display omitted] Phosphate material LiMnPO4 is popular for its high energy density (697 W·h·kg−1) and safety. When LiMnPO4 crystal grows, the potential barrier along b and c axis is strong, which makes the crystal grow along b axis to form a one-dimensional chain structure. However, the main migration channel of lithium ions in olivine structure is plane (0 1 0). By shortening the growth in the direction of b axis and enhancing the diffusion along the directions of a and c, two-dimensional nanosheets that are more conducive to the migration of lithium ions are formed. The dosage of polyols is the key factor guiding the dispersion of the crystals to the (0 1 0) plane. X-ray diffraction (XRD), Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and other means are used to characterize the samples. After experiments, we found that when the ratio of polyol/water was 2:1, the morphology of the synthesized sample was 20–30 nm thick nanosheets, which had the best electrochemical performance. At 0.1C, the discharge specific capacity reaches 148.9 mA·h·g−1, still reaches 144.3 mA·h·g−1 at the 50th cycle. and there is still 112.5 mA·h·g−1 under high rate (5C). This is thanks to the good dispersion of the material in the direction of the crystal plane (0 1 0). This can solve the problem of low conductivity and ionic mobility of phosphate materials.